2016
DOI: 10.1002/cmdc.201600529
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐Based Drug Design of Mineralocorticoid Receptor Antagonists to Explore Oxosteroid Receptor Selectivity

Abstract: The mineralocorticoid receptor (MR) is a nuclear hormone receptor involved in the regulation of body fluid and electrolyte homeostasis. In this study we explore selectivity triggers for a series of nonsteroidal MR antagonists to improve selectivity over other members of the oxosteroid receptor family. A biaryl sulfonamide compound was identified in a high-throughput screening (HTS) campaign. The compound bound to MR with pK =6.6, but displayed poor selectivity over the glucocorticoid receptor (GR) and the prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“… a Affinity of compounds for the partially purified human full length GR determined in a fluoroligand binding assay using the fluorescent polarization method b Affinity of compounds for the progesterone receptor (PR) expressed in human T47D cells and the human androgen receptor (AR) expressed in LNCaP cells, were determined in a radioligand binding assay …”
Section: In Vitro Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation
“… a Affinity of compounds for the partially purified human full length GR determined in a fluoroligand binding assay using the fluorescent polarization method b Affinity of compounds for the progesterone receptor (PR) expressed in human T47D cells and the human androgen receptor (AR) expressed in LNCaP cells, were determined in a radioligand binding assay …”
Section: In Vitro Pharmacologymentioning
confidence: 99%
“… b Affinity of compounds for the progesterone receptor (PR) expressed in human T47D cells and the human androgen receptor (AR) expressed in LNCaP cells, were determined in a radioligand binding assay c Affinity of compounds for the human mineralcorticoid receptor (MR) ligand binding domain determined in scintillation proximity assay (SPA) d Affinity of compounds for the agonist site of the human estrogen receptor α (ERα) and human estrogen receptor β (ERβ) expressed in transfected Sf9 cells determined in a fluoligand binding assay using the fluorescence polarization method.…”
Section: In Vitro Pharmacologymentioning
confidence: 99%
“…luciferase human MR reporter gene antagonist assay (hMR GAL4 ). 46 Docking of (R)-5 into the induced-fit model of MR in complex with 4 indicated that (R)-5 extended into all three regions of our pharmacophore model (Figure 2C). However, rac-5 exhibited poor kinetic solubility, pSol > 6.0, and low metabolic stability in human liver microsomes (HLMs) with CL int values of 120 μL/(min mg).…”
Section: ■ Results and Discussionmentioning
confidence: 92%
“…Selection was done by substructure searches using motifs from known binders targeting the three key regions mentioned above. Subsequent iterative screening of the selected compounds provided a series of sulfonamide benzoxazinones, as exemplified by rac -5 with pIC 50 5.2 and an efficacy extrapolated to 100% in a GAL4 luciferase human MR reporter gene antagonist assay (hMR GAL4 ) . Docking of ( R ) -5 into the induced-fit model of MR in complex with 4 indicated that ( R ) -5 extended into all three regions of our pharmacophore model (Figure C).…”
Section: Resultsmentioning
confidence: 99%
“…. 57 (13). A mixture of compound 11 (152 mg, 0.4 mmol), compound 19 (122 mg, 0.48 mmol), potassium carbonate (221 mg, 1.6 mmol), and [1,1'bis(diphenylphosphino)ferrocene]dichloropalladium(II), complex with dichloromethane (33 mg, 0.04 mmol) in dioxane/H2O (v/v= 9:1, 2 mL) was stirred at 90 o C under nitrogen atmosphere.…”
Section: (R)-3-(3-fluoro-4-(isoxazol-4-yl)phenyl)-5-(hydroxymethyl)ox...mentioning
confidence: 99%